SWOT Analysis of Organic Waste Crushing Mechines Using Grounded Theory - Dwi Ramadona, Dasatry; Fitria, Yossa; Nazmi, Fittria; Heikal, Jerry (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
Garbage is the residue of human daily activities and/or natural processes in solid form. Waste can come from various activities such as household waste, agricultural waste, building waste, trade and office waste, and industrial waste. The amount of waste stockpiles in Payakumbuh City until June 2023 is 100,386 tons per day. With details (1) Waste transported to the Final Processing Site (TPA) every day is 83,862 tons without segregation, (2) Waste processed at TPS3R is 0.252 tons with 6 units of equipmen, (3) Management at the unit waste bank 0.041 tons, (4) management at the main waste bank 7 tons, (5) Informal sector/ lapak as much as 7.4 tons, (6) Magot as much as 0.31 tons, (7) A total of 1.52 tons of waste has not been managed properly. Of the total amount of waste disposed of at the Temporary Final Processing Site (TPAS), 60 percent is organic waste. This study uses a qualitative technique with a grounded theory approach. The author conducted direct interviews with internal parties (Bappeda Payakumbuh City) and external parties (Tool Manufacturers, Equipment Users and the Environment Agency) to determine the impact of using a mobile organic waste counter machine in reducing the amount of organic waste in Payakumbuh City. Based on the research results, it was found that the coding scheme consisted of 41 codes that formed 9 categories and gave rise to 4 themes with a total score of 41. The highest score in coding was 23 on the theme of technology use. So it can be concluded that the use of technology greatly affects the reduction of organic waste in Payakumbuh City.